PEMBERDAYAAN PENYULUH AGAMA DALAM PENINGKATAN PELAYANAN KEAGAMAAN KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA TIMUR - Muchtar Muchtar (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
Religious counseling activities in Indonesian society has a very strategic function. The research problem is as follows : How does implementation of the decision of the Coordinator Minister for Development Monitoring and states apparatus, number: 4/KEP/MK.WASPAN/9/1999? ; What are the efforts that been made by the government in improving the competence of religious counselor?; What is factors that drive and inhibit the religious counselor in carrying out its duties and functions ?; How is the public perception about religious counselor in carrying out its duties and functions? The main source of the data of this research are observation, in-depth interviews, focus group discussion, literature and document review. The research methode used in this study was qualitative research methods.